Lapland's Push and Pull Factors - Sandholm, Milla (Lapin ammattikorkeakoulu, 2018)
The purpose of this thesis was to study Lapland’s push and pull factors, because it was established that Lapland keeps attracting applicants even after a tuition fee for non-EU and ETA countries was introduced in 2017, raising an interest to study what factors motivate people to come to Lapland. The aim was to give the reader a basic understanding of Lapland and its major sources for the flow of people: tourism, studies and migration. For the theoretical background, tourism motivation, push and pull factors and how they can be seen in tourism, studies and migration were studied. Three Lappish companies’ marketing alongside with the marketing of Lapland University of Applied Sciences and University of Lapland were researched, to see how the Lappish factor and pull forces are being utilized. The data collected for this thesis included a survey that reached 21 international students and another small questionnaire aimed to the marketing employees of the schools in question. The survey’s audience was limited to only international students, as an image of Lapland was wanted through their eyes. This thesis used qualitative research methods in analysing the material. The results of the survey indicate that the students are generally drawn to Lapland for the experience and the great education in Finland. Most felt pleased with their studies, however some critique came up that could possibly be researched further. It was also established, what specifically are the push and pull factors that affect Lapland, and how they vary in different cases and people. Tämän opinnäytetyön tarkoituksena oli tutkia Lapin työntö- ja vetovoimatekijöitä, sillä huomattiin, että Lappi houkuttelee yhä hakijoita jopa sen jälkeen, kun vuonna 2017 EU:n ja ETA:n maiden ulkopuolisille hakijoille tuli lukuvuosimaksut, mikä herättikin kiinnostuksen tutkia, mitkä tekijät motivoivat ihmisiä tulemaan Lappiin. Lukijalle haluttiin antaa perustavanlaatuisen ymmärryksen Lapista ja sen suurimmista ihmisvirtalähteistä: turismista, opinnoista ja ...